Harnessing microbial communities for enhanced plant resilience against diseases - Sulieman, Abdel Moneim E.; Al-azmi, Meshari; Alanazi, Naimah Asid; Ghoniem, Ahmed Eisa; Hasan, Mohamed El-Sayed; Alothman, Norah S.; Alrashidi, Ayshah (Frontiers in Microbiology, 2025)
BackgroundPhytophthora infestans (P. infestans) and other plant infections threaten global agriculture and food security. This research incorporated Pseudomonas strains in microbial consortia to boost plant tolerance to P. infestans. The P. infestans fungus causes collapse and deterioration in many crops like potatoes by quickly spreading through their tubers and leaves in warm, damp weather.ObjectiveThe main goals were to identify effective Pseudomonas strains (those with high inhibitory activity), test their interactions (both inhibitory and synergistic), and determine the effect of inoculum density on disease treatment.MethodsWe used the following methodologies, from potato shoots and rhizosphere samples, Nine different strains of the antifungal bacterium Pseudomonas which were identified with preliminary antifungal activity. Bintje showed the greatest resistance to P. infestans among the three potato types that were examined. Methods utilized comprised: Quantification of bacterial density and growth, the inhibitory assays for P. infestans, experiments on leaf disc infections, Assessing the severity of an infection, Analysis of zoospore discharge. Studies on the integrated development of bacteria and valuation using statistical methods.ResultsThe study revealed the complexity of microbial interactions, host-specific reactions, and cell density's impact on treatment success. The study suggests using Pseudomonas strains as biocontrol agents, advancing sustainable agriculture. Microbial consortia disease management requires advanced methodologies, according to the findings. Investigating long-term ecological impacts on soil health, microbial diversity, and crop yield sustainability; validating identified microbial consortia through field trials; evaluating scalability and economic viability; and researching genetic engineering for customized disease control are recommended.ConclusionsResults suggest a shift from chemical pesticides to environmentally friendly plant disease control considering its ethical and regulatory implications. This study emphasizes the intricacy of microbial interactions and the need for informed biocontrol decisions. Their study also increases ecological knowledge and encourages innovative, sustainable worldwide agriculture.